1992
DOI: 10.1136/qshc.1.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Prospective audit comparing ambulatory day surgery with inpatient surgery for treating cataracts.

Abstract: Objectives -To compare the cost effectiveness and safety of inpatient cataract surgery (with one night in hospital postoperatively) with ambulatory day case surgery under local anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…8 Twenty-four-hour ambulatory care in other specialities is well established. [9][10][11] Day case surgery has been found to be safe in a variety of specialties including gynaecology, orthopaedics and general surgery. 12 Early discharge for many minor gynaecological procedures has significant advantages for the patient and the healthcare provider alike.…”
Section: Discussionmentioning
confidence: 99%
“…8 Twenty-four-hour ambulatory care in other specialities is well established. [9][10][11] Day case surgery has been found to be safe in a variety of specialties including gynaecology, orthopaedics and general surgery. 12 Early discharge for many minor gynaecological procedures has significant advantages for the patient and the healthcare provider alike.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have been conducted with a primary focus on patient acceptance and preferences in terms of QoL comparing day-case surgery and inpatient surgery [ 7,[23][24][25] and between minimally invasive and traditional open treatment [12]. These studies found that patients' acceptance, in terms of QoL, is similar in both types of procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus if one procedure emerges as less costly and of equal or greater effectiveness than all the other options on each dimension of effectiveness, it is clearly the most cost effective option. For example, Percival and Setty, in their comparison of day surgery with ovemight inpatient care for cataract surgery, measured outcomes in terms of the number of both operative and postoperative complications, and in terms of visual acuity of patients three to six days and 10 weeks to six months after surgery. '0 Patient satisfaction was also elicited through a questionnaire.…”
Section: Measures Ofeffectivenessmentioning
confidence: 99%